2014
DOI: 10.1177/0898264314531616
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Social Isolation in Community-Dwelling Elderly by Differences in Household Composition and Related Factors

Abstract: The aim of this study was to measure the prevalence of social isolation in community-dwelling elderly and related factors based on household composition differences. Method: We used the six-item Lubben Social Network Scale to measure social isolation in 2,000 individuals. Multiple

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 20 publications
2
31
2
Order By: Relevance
“…48 However, our result is well-supported by several studies reporting similar negative impacts on cognitive function among Asian older adults who live in multigenerational family households. 12,15,49 For instance, Ibrahim et al found severe cognitive impairment among older adults living with their children and grandchildren in Malaysia. 50 They found that the older adults were socially isolated and lacked intellectual interactions despite living in a large family household.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48 However, our result is well-supported by several studies reporting similar negative impacts on cognitive function among Asian older adults who live in multigenerational family households. 12,15,49 For instance, Ibrahim et al found severe cognitive impairment among older adults living with their children and grandchildren in Malaysia. 50 They found that the older adults were socially isolated and lacked intellectual interactions despite living in a large family household.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] Several empirical studies have shown that social engagement can maintain cognitive abilities even in old age and lower the risk of dementia. 12,13 Researchers suggest these older adults likely benefit from intellectual stimulation obtained through daily social interactions, 14 and household living environments have considerable influence over the course of interpersonal exchanges and social resources (i.e. instrumental, informational, and emotional support) available to an older adult.…”
Section: Introductionmentioning
confidence: 99%
“…Some writers have noted there are as many different definitions and operationalizations of social isolation as there are social isolation researchers (Shimada, Yamazaki, Nakano, & Ngoma, 2014). What is generally agreed upon, however, is that social isolation is multi-dimensional and is conceptualized as having two domains: objective and subjective (Cornwell & Waite, 2009a, 2009b; Elder & Retrum, 2012; Nicholson, 2009; Pedersen, Andersen & Curtis, 2012).…”
Section: Conceptualization and Measurement Of Social Isolationmentioning
confidence: 99%
“…7 For a significant minority of these people, however, a common negative aspect of old age is that of social isolation. 8 , 9 A recent national survey in Malaysia, a neighboring country to the study site, reported that 48.6% of old persons were at risk of social isolation and that the oldest old persons were at higher risk. 10 , 11 Research in Korea, Singapore, and the People’s Republic of China also investigated social connectedness of elderly people in each society.…”
Section: Introductionmentioning
confidence: 95%